2017
DOI: 10.1016/j.semcdb.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cell biology of complement membrane attack

Abstract: The membrane attack complex (MAC) is the pore-forming toxin of the complement system, a relatively early evolutionary acquisition that confers upon complement the capacity to directly kill pathogens. The MAC is more than just a bactericidal missile, having the capacity when formed on self-cells to initiate a host of cell activation events that can have profound consequences for tissue homeostasis in the face of infection or injury. Although the capacity of complement to directly kill pathogens has been recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 77 publications
0
49
0
3
Order By: Relevance
“…In order to improve both quantitative and qualitative assessments of the erythroid component in PNH we have introduced CD71 (transferrin receptor) as a marker of immature RBCs (iRBC) and examined the utility of assessing the clone size within this fraction and whether a clearer delineation of Type II and Type III cells can be made. iRBCs are unaffected by complement‐mediated lysis (Morgan et al, ; Sadallah et al, ) or by transfusions of mature RBCs (Thomson‐Luque et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve both quantitative and qualitative assessments of the erythroid component in PNH we have introduced CD71 (transferrin receptor) as a marker of immature RBCs (iRBC) and examined the utility of assessing the clone size within this fraction and whether a clearer delineation of Type II and Type III cells can be made. iRBCs are unaffected by complement‐mediated lysis (Morgan et al, ; Sadallah et al, ) or by transfusions of mature RBCs (Thomson‐Luque et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Since immature PNH RBCs are not hemolyzed by activated complement (Morgan, Boyd, & Bubeck, 2017;Sadallah, Hanno, & Schifferli, 2010) and are not significantly diluted by transfusions of mature RBCs, other authors have proposed to assess immature RBC (nucleated RBCs and/or reticulocytes). A variety of flow cytometry assays have been developed to achieve this.…”
mentioning
confidence: 99%
“…[ 31 ] All the complement pathways activate a cascade of events such as the membrane attack complex (MAC), anaphylatoxins (C3a, C4a, and C5a), and opsonins (C3b, C4b, and C1q). [ 32 ] These mediators have the following functions: i) MAC forms a transmembrane channel in the phospholipid bilayer that lead to the lyses and thereby death of targeted cells; [ 33 ] ii) anaphylatoxins generate a local inflammatory response through the degranulation of endothelial cells, mast cells and phagocytes; iii) opsonins increase the phagocytosis rate of xenobiotics. [ 34 ]…”
Section: Complement System Activationmentioning
confidence: 99%
“…[16][17][18] However, the exact molecular mechanism by which MAC pores kill Gram-negative bacteria remains largely unknown. These studies have revealed the overall dimensions of the MAC and provided structural insights into how the MAC ruptures single-membrane particles, such as liposomes and erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed the overall dimensions of the MAC and provided structural insights into how the MAC ruptures single-membrane particles, such as liposomes and erythrocytes. [16][17][18] However, the exact molecular mechanism by which MAC pores kill Gram-negative bacteria remains largely unknown. The cell envelope of Gram-negative bacteria consists of an outer membrane (OM) that contains a large amount of lipopolysaccharides (LPS), an inner membrane (IM), and a peptidoglycan (PG) layer in between.…”
Section: Introductionmentioning
confidence: 99%